Effectiveness of Smart Governance Implementation in Supporting Public Services in Batam City - Indri Anggi Simatupang; Timbul Dompak; Lubna Salsabila; Karol Teovani Lodan (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2024)
This study evaluates the efficacy of Smart Governance implementation in enhancing public services in Batam City. Smart governance, a principal facet of the smart city paradigm, seeks to enhance efficiency, transparency, responsiveness, and accountability by the utilisation of information technology. Batam City, strategically positioned as an economic and trade hub, is dedicated to implementing smart governance concepts to enhance the quality of its public services. This research employs a descriptive methodology with qualitative analysis to assess the strategic measures implemented, including the digitalisation of public services, transparency and budget management, integrated data management, and enhanced community participation.The findings indicate that the adoption of smart governance in Batam has effectively enhanced administrative efficiency and transparency in public services. Nonetheless, difficulties such as the digital infrastructure deficit in remote regions and insufficient digital literacy within the population remain significant impediments. This research recommends enhancing digital infrastructure, creating more user-friendly applications, and implementing digital literacy training programs for the community. With an appropriate strategy, Batam City may persist in advancing Smart Governance as a sustainable smart city paradigm.